Hubungan Motivasi terhadap Tingkat Stress Mahasiswa dalam Menulis Tugas Akhir - Helena Nduru; Siti Nursalimah; Sepdina Candra Putri; Sri mulyeni (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Students experience a decline in motivation to complete their final projects, primarily due to high levels of stress. This article aims to examine the relationship between motivation and students’ stress levels in writing their final projects, as well as to identify strategies for enhancing motivation and reducing stress during the final project writing process. This research employs a qualitative approach and is conducted as a literature review. The data were collected from the Google Scholar database without specifying the year of publication. The data analysis technique used in this study is content analysis. The findings indicate that motivation has a significant relationship with students’ stress levels in writing their final projects. Motivation arises from both internal and external sources and tends to decline when stress levels increase. Stress occurs due to various factors, such as procrastination, ineffective supervision by academic advisors, and students’ limited writing skills. To enhance students’ motivation, academic advisors play a crucial role in providing effective guidance; writing workshops are also necessary to improve students’ writing skills, increase their confidence, and provide social support that is relevant to students’ needs. Strategies to reduce stress include avoiding procrastination, practicing effective time management, and engaging in self-coping strategies. This study contributes to assisting students and higher education institutions in reducing unproductive behaviors in final project writing among final-year students.